Evaluasi Kualitas Aplikasi Mobile Commerce KamiMart berbasis Android berdasarkan Standar ISO/IEC 25010 - Febryan Asa Perdana; Herman Tolle; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
KamiMart is a retail business unit or division in a form of minimarket which is owned by worker cooperatives (Kopkar) of PT. Paiton Operation & Maintenance Indonesia (POMI). Currently, KamiMart is experiencing a decline in sales due to the corona virus disease (COVID-19) pandemic, and forced KamiMart to adapt to the situation and develop a strategic move to keep thriving. KamiMart is being handicapped to deal with the mentioned problem as it heavily relies on storefront or offline sales. Hence, KamiMart decided to take strategic measure by developing a mobile commerce (m-commerce) application. Given that the m-commerce app has a very important role and value proposition for both KamiMart and its customers, the quality of the app must be considered and ensured as much as possible, one of which is through a quality evaluation of the mentioned app. From the quality evaluation result, it can be concluded that KamiMart m-commerce app has a very good or outstanding quality as it obtains 97,82% for overall app quality value that is constructed from the following values: 98,76% for Functional Suitability, 98,75% for Usability, 97,69% for Performance Efficiency, 100% for Reliability, 99,6% for Maintainability, 100% for Portability, and 90% for Security.